PENERAPAN BUDAYA RELIGIUS PADA SISWA KELAS X DI MAN 1 TULUNGAGUNG - apriliani, widia; Maunah , Binti (ILJ: Islamic Learning Journal, 2024)
Religious culture is a way of thinking or acting that is based on overall religious values. It can also be said that religious culture is manifested from the values ??of religious teachings which are used as traditions in behavior and are followed by school members. Religious culture has an important role and is one of the efforts that can be used as an alternative support in supporting education in Indonesia. The focus of this research is to determine the application of religious culture in first grade at Islamic High School 1 Tulungagung. This research uses a qualitative research approach and the type of research used is case study and descriptive research. In this research, data collection was based on three parts, namely person, place and paper. The data collection techniques used participant observation, in-depth interviews and documentation. The results of this research found that the religious culture applied to class, weekly (Tahfidzul Qur'an program and activities for memorizing short surahs as well as daily prayers and the prophet's blessings), monthly (Tahsin Qur'an and study of yellow book of Fiqh Fathul Qorib), annual (PHBI, Islamic Boarding School and Haji rituals), and incidentally (Istighasah). There is also a 5S religious culture, namely Smiling, Egards, Greet, Be polite and Courteous. In implementing the religious culture of first grade students, it is implemented through the habits that have been carried out and an example of the teachers regarding disciplinary attitudes implemented in madrasah.